Forensic social work: The Construction of Possible Ways of Conducting a Criminal Intervention - Utrera, María de las Mercedes (Latin American social work in the justice system, 2023)
Social work in the field of justice in the province of Buenos Aires, Argentina, has a long tradition of intervention. It is an occupational space that has been growing, and changing along with legal changes and transformations of jurisdictional bodies. Likewise, social workers in the law of professional practice have been modulating and configuring the complex field of intervention, which has been subjected to tensions and is always undergoing construction. Nowadays, the profession of social work has a high level of representation in legal activity (Asesorías Periciales de la SCJPBA), more than the other traditional professions, and the expert production of social workers is almost inescapable in all jurisdictions (criminal, juvenile criminal, civil, and family jurisdictions). This chapter will consider intervention as a strategy that social workers can use in the elaboration of social expertise. Forensic social work is tasked with social control, and in an institution born with such purposes, it maximizes relative autonomy. We will describe that the history and actual state of expert interventions made by forensic social workers in carrying out justice in the province of Buenos Aires. We will also point out the particular considerations of experts, such as viability and possibility instruments that are linked in particular to interventions in the criminal jurisdiction for adults and more specifically to the social evaluations that grant criminals an early exit, before they have served the entirety of their sentences.